2017
DOI: 10.4172/2155-952x.1000262
|View full text |Cite
|
Sign up to set email alerts
|

A Review on The Bioconversion of Lignin to Microbial Lipid with Oleaginous Rhodococcus opacus

Abstract: Rhodococcus opacus produces intracellular lipids from the biodegradation of lignocellulosic biomass. These lipids can be used to produce biofuels that could potentially replace petroleum-derived chemicals. Current studies are focusing on deconstructing lignin through efficient and cost-effective pretreatment methods and improving microbial lipid titers. R. opacus can reach high levels of oleaginicity (>80%) when grown on glucose and other aromatic model compounds but intracellular lipid production is much lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…The application of lignocellulosic fibers in bioplastics has been investigated in several studies which mainly focus on cellulose fiber. Several reviews published recently can provide the readers with more detailed information [11,136]. Unmodified fibers can serve as a cheaper material compared to cellulose modification, therefore, the application of raw lignocellulosic fibers in bioplastics has attained more attentions in recent years [11].…”
Section: Application Of Lignocellulosic Fibers In Bioplasticsmentioning
confidence: 99%
“…The application of lignocellulosic fibers in bioplastics has been investigated in several studies which mainly focus on cellulose fiber. Several reviews published recently can provide the readers with more detailed information [11,136]. Unmodified fibers can serve as a cheaper material compared to cellulose modification, therefore, the application of raw lignocellulosic fibers in bioplastics has attained more attentions in recent years [11].…”
Section: Application Of Lignocellulosic Fibers In Bioplasticsmentioning
confidence: 99%
“…Generally, oleaginous organisms can accumulate > 20% of their dry cell weight (DCW) as lipids. In recent years, researchers found that some oleaginous microbes can synthesize lipid from lignin-based aromatics and Rhodococcus is such a promising species among these microbes, because of its robust growth, tolerance to various aromatics, broad substrate specificity, as well as robust lipid production capability [96, 97]. As mentioned in the “Degradation pathways of lignin-based aromatics in bacteria”, Rhodococcus bacteria can metabolize various lignin-based aromatics.…”
Section: Application Of Multiple Metabolic Pathways For Lignin Valorimentioning
confidence: 99%
“…121 Kosa Using fed-batch fermentation of T. cutaneum, these researchers increased the cell density from 2.4 to 5.1 g/L and the final lipid concentration reached 0.85 g/L compared to 0.4 g/L in batch mode. Extensive studies have proven that Rhodococcus species can grow on lignin materials, including aromatic compounds, technical lignin, and lignocellulose to accumulate lipid.…”
Section: Microbial Lipidsmentioning
confidence: 99%
“…Extensive studies have proven that Rhodococcus species can grow on lignin materials, including aromatic compounds, technical lignin, and lignocellulose to accumulate lipid. 121 Kosa and Ragauskas 98 explored two strains of R. opacus DSM 1069 and R. opacus PD 630 on their abilities of using lignin model compounds, and the researchers showed that these two strains were able to grow on 4-hydroxybenzoic acid and vanillic acid at the concentration 0.5% The mutant strain, Amycolatopsis sp MA-2, generated from muconate cycloisomerases gene deletion, accumulated 3.1 g/L muconic acid from guaiacol within 24 hr, achieving a yield of 96%; MA-2 also produced 1.0 mM muconic acid from pine lignin hydrolysate within 10 hr with a molar yield of 72%.…”
Section: Microbial Lipidsmentioning
confidence: 99%